State Culture Capital Foundation Importance Work Strategy for Support of Education and Professional Qualification Development of Creative Personality of Visual Arts - Vīgnere, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In national culture politics, one of the most urgent issues in provision of creative process, creative activity and professional development of artists is the insufficient funding for culture. State budget resources via the State Culture Capital Foundation are diverted for the needs of culture and arts with the aim – provide such environment of arts and culture in Latvia that would strengthen and increase the value of creative capital of culture and facilitate participation of as large part of society as possible in the cultural processes so that to help everyone to understand and analyse the world, to be flexible and open to changes. The work analyses the work strategy and tasks of State Culture Capital Foundation, volume of project competition funding, its usefulness and results, also indicators of cultural policy in work of foundation.